Customer Satisfaction in Hotel Cinta Sayang Resort, Sungai Petani, Kedah, Malaysia: a Qualitative Approach - Rabean, Qistina binti; Haji-Othman, Yusuf (Prosiding Seminar; 2019: 2019 International Conference of Interdisciplinary Sciences, 2020)
The abstract is to examine customer satisfaction in hotel industry among customer at Hotel Cinta Sayang Resort in the state of Kedah, Malaysia using a quantitative approach. This research is to identify what is the factor that influences customer satisfaction in hotel industry. There are a few objectives for this research which are to identify the relationship between tangible, reliability, responsiveness, confidence and communication toward customer satisfaction. By using a questionnaire method, all 30 questionnaires complete by 30 respondents and this questionnaire is valid for further analysis this study finds that the satisfactions in hotel are tangible, reliability, responsiveness, confidence and communication. From the findings, most of the factors are fairly influencing customer satisfaction were identified. This study recommends more explorations in the area of hotel industry using a quantitative approach and future studies should focus on internal or psychological factor of customer satisfaction.